Extracting route information from hand-drawn map using fuzzy vector - Boonyarit Samakrob (2018)
One possible way to describe a direction among human is to use rough hand-drawn map indicating the path from the start to goal positions. In this paper, we build a system to help human communicate with the robot the same way. In particular, we create a graphic user interface and translate the route direction into linguistic description using fuzzy vector analysis. The movement command for each important point is generated as well. The experimental results demonstrate that our system performs similar to human thinking. © 2012 IEEE.